2001
DOI: 10.1021/jm001121c
|View full text |Cite
|
Sign up to set email alerts
|

Ether Phospholipid-AZT Conjugates Possessing Anti-HIV and Antitumor Cell Activity. Synthesis, Conformational Analysis, and Study of Their Thermal Effects on Membrane Bilayers

Abstract: The 1-O-hexadecyl-2-O-methyl-sn-glyceryl phosphodiester AZT 4 and hexadecyl-phosphodiester AZT 5 derivatives were synthesized and found to be active against HIV-1, HIV-2, and tumor cell proliferation. Compared to AZT, compound 4 possessed ca. 10-fold lower anti-HIV activity and ca. 10-fold higher anti-tumor cell activity. Compound 5 was 10-fold less potent than compound 4 in both biological tests. In an attempt to correlate biological activity of compounds 4 and 5 with structure, their conformational and therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…[26] Interesting work has also been carried out with synthetic phospholipid-AZT conjugates and their effects on HIV replication. [27,28] Of further interest in respect of the hydrophobic trityl group, is the interesting work reported by Cushman and co-workers [29] on the synthesis and biological evaluation of some alkenyl diaryl methanes (ADAMS). These compounds behave as NNRTIs.…”
Section: Resultsmentioning
confidence: 99%
“…[26] Interesting work has also been carried out with synthetic phospholipid-AZT conjugates and their effects on HIV replication. [27,28] Of further interest in respect of the hydrophobic trityl group, is the interesting work reported by Cushman and co-workers [29] on the synthesis and biological evaluation of some alkenyl diaryl methanes (ADAMS). These compounds behave as NNRTIs.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that dietary GG influences gut development and protection by enhancing EPL content, which has a preventative role in carcinogenesis [21,22,47], inflammation [39][40][41]48] and lipid oxidation [25,26,49]. The rate of metabolic conversion from GG to EPL in the intestine is not known.…”
Section: Discussionmentioning
confidence: 99%
“…One type of EPL known as plasmalogen, 1-O-alkenyl-2-acylglycero-phospholipids, accounts for about 6 -12% of ethanolamine phosphoglyceride (EPG) in rat intestinal mucosa [15,16]. A high content of EPL may contribute to maintenance of cell integrity and function [17][18][19][20][21][22][23] such as permeability [18], fluidity [24] and endogenous antioxidant for membrane peroxidation [25,26]. Ether phospholipid also induces cell apoptosis [17], cytotoxicity [19,20] and antitumor activity [21][22][23], which could have potential in anticancer applications.…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks of nucleoside therapeutics provoke a profound interest in the search of prodrugs exhibiting an effectiveness superior to that of the parent drug. Among such derivatives, conjugates of nucleosides and phospholipids attracted attention and it was demonstrated that these derivatives display advantageous biological properties over free nucleosides (Ryu et al 1982;Shuto et al 1995;Vodovozova et al 1996;Herrmann et al 1997;Brachwitz et al 1998Brachwitz et al , 1999Kucera et al 1998;Mavromoustakos et al 2001;Alexander et al 2003; for a review, see Morris-Natschke et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical synthesis of phospholipid-D-nucleo side conjugates has been achieved (Brachwitz et al 1998(Brachwitz et al , 1999Mavromoustakos et al 2001;Alexander et al 2003; for a review, see Rosemeyer 2005) though enzymatic and chemo-enzymatic methods also exist (Shuto et al 1995, and references cited therein). An application of PLD as a biocatalyst for the preparation of such conjugates is very efficient (Shuto et al 1995) and these data prompted us to study an enzymatic synthesis of nucleoside-phospholipid conjugates employing phospholipase D (PLD; EC 3.1.4.4) as a biocatalyst.…”
Section: Introductionmentioning
confidence: 99%